Эффективность осаждения пыли полем коронного разряда при различных типах питающего напряжения - Богуславский, Л. З. (НТУ "ХПИ", 2014)
Рассмотрены вопросы эффективности улавливания пыли из промышленных газовых выбросов путем электростатической фильтрации, при одновременном питании коронного разряда в технологическом объеме различными типами постоянного, переменного и импульсного напряжения. Установлена взаимосвязь между длинной пролета частиц пыли по зоне фильтрации и эффективностью фильтрации. Экспериментально подтверждена квадратичная форма зависимости эффективности осаждения от величины питающего напряжения. Установлено повышение эффективности осаждения пыли при использовании комбинированного питания.

The efficiency of dust removal from industrial wasted gases by electrostatic precipitation during corona discharge feeding bydifferent types of high voltage is considered. Theoretically substantiated using particles passage length by an active zone like precipitation efficiency factor. The experimental values of particles passage length for various levels of DC voltage and for various frequency of combined voltage is carried out. The results shown that the AC voltage and pulse voltage does not able to hold dust removal efficiency on required level. But dust deposition gain is proved by using of DC voltage and pulsevoltage superposition. Dust removal efficiency increases with reduction of electrical power consumption is provenin case of DC voltage and pulse voltage superposition.
The dust removal efficiency by corona discharge field with various source voltages forms
Keywords: электростатическая фильтрация; длина пролета частиц; скорость дрейфа; форма питающего напряжения; electrostatic precipitation; particles passage length; migration velocity